China’s grand strategy within 21st-century megatrends - Bartha, Zoltán (Észak-magyarországi Stratégiai Füzetek, 2024)
The main aim of this study is to identify possible components of China’s grand strategy and check how they can influence global megatrends. Based on a literature review, four grand strategy components are identified: 1) building up military power, 2) consolidating power at the peripheries and pushing for more control over disputed territories, 3) expanding economic influence through the Belt and Road Initiative, and 4) establishing new standards in digital technologies and promoting cyber sovereignty. These strategic tools can directly affect the following megatrends that are commonly mentioned in the literature: shift of economic power, emerging markets, new economic order; digitalisation; globalisation; deglobalization, trade reduction; diversity of governance, trust in the political system; and scarce resources. Using data taken from Google Trends it is shown that in the 2004-2023 period the trends of Chinese grand strategy terms correlate most with terms that represent the following three megatrends: digitalisation, globalisation, and scarce resources.